2008
DOI: 10.1007/s00268-008-9716-4
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between the Method of Sympathetic Ablation for Palmar Hyperhidrosis and the Occurrence of Compensatory Hyperhidrosis: A Review

Abstract: The compiled results published so far in the literature do not support the claims that lowering the level of sympathetic ablation, using a method of ablation other than resection, or restricting the extend of sympathetic ablation for primary palmar hyperhidrosis result in less CHH. In the future, standardization of the methods of retrieving and reporting data are necessary to allow such a comparison of data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 195 publications
1
29
0
Order By: Relevance
“…One of most troublesome side effects of thoracic sympathectomy is compensatory sweating, which interferes with the patient's quality of life and causes patient dissatisfaction [9][10][11]. Chang et al demonstrated that the degree of patient satisfaction is significantly inversely related to the severity of compensatory sweating after sympathectomy, which supports our results [12].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One of most troublesome side effects of thoracic sympathectomy is compensatory sweating, which interferes with the patient's quality of life and causes patient dissatisfaction [9][10][11]. Chang et al demonstrated that the degree of patient satisfaction is significantly inversely related to the severity of compensatory sweating after sympathectomy, which supports our results [12].…”
Section: Discussionsupporting
confidence: 88%
“…Besides compensatory sweating, reoccurring postoperative palmar hyperhidrosis and excessive 8 dry hands are other influential factors that influence the degree of postoperative patient satisfaction [9,10]. It is natural for patients to feel dissatisfaction if palmar hyperhidrosis recurs.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons believe that the rate of CS depends on the level and extent of sympathectomy, with a larger and higher resection of sympathetic chain resulting in a higher incidence of CS [54,55]. Conversely, some believe that CS occurs independent of the extent of sympathectomy [56,57]. Regardless of the mechanism, many surgeons have altered their surgical technique from resecting the sympathetic chain to clipping in the hopes that the procedure could be reversed if a patient develops severe CS.…”
Section: Complications and Side Effects Of Endoscopic Thoracic Sympathementioning
confidence: 99%
“…This review, which includes articles from the last decade, comes to a conclusion regarding the best level of sympathetic ablation for the treatment of primary palmar hyperhidrosis shared by many authors (T3). However, in a thorough review (246 references) on the subject comparing the correlation of the method for sympathetic ablation with the subsequent occurrence of compensatory sweating [2], the authors could not define any such correlation.…”
Section: To the Editormentioning
confidence: 99%